A qualitative method for testing the antimicrobial ability of osteosynthetic fixation material by simulating in vitro contamination by Staphylococcus aureus - Pruchova, Eva; Kosova, Michaela; Jarolimova, Petra; Kumherova, Monika; Fojt, Jaroslav; Kryll, Vladimir; Joska, Ludek (Folia microbiologica, 2020)
External fixators of serious fractures could be an attractive substrate on which microorganisms can accumulate. Therefore, this study aimed to develop a suitable method for enabling the simulation of a real situation when osteosynthetic fixation material is open for the potential threat of bacterial attack. Agar-based media represented human tissue, and the metallic pin characterized the screw in the fixation. Various types of agar, supplements, and contamination strategy by Staphylococcus aureus were tested. The influence of the initial bacterial concentration was also examined. Surfaces were observed by scanning electron microscopy (SEM), and all results were compared. Brain Heart Infusion Agar with the Egg Yolk Tellurite Emulsion was established in a transparent test tube as a suitable system for enabling the good interpretability of bacterial contamination in the pin's surroundings. Pin contamination has been found to be an appropriate approach for testing microbial growth, rather than agar surface contamination, which distorted obtained results. A lower initial colony forming units (CFU) provided better clarity of the test. SEM observation of the pin surface was comparable with the visual evaluations in the test tubes. Results were assembled for positive and negative control samples as well. Screening method for the most common bacteria S. aureus has been standardized and developed. This experimental setup could also be a useful tool for surface modification with antibacterial properties testing.
Keywords: antibakteriální látky; External Fixators; Microscopy, Electron, Scanning; externí fixátory; počet mikrobiálních kolonií; biofilmy; Culture Media; Equipment Contamination; Colony Count, Microbial; lidé; Staphylococcus aureus; mikroskopie elektronová rastrovací; Anti-Bacterial Agents; kontaminace zdravotnického vybavení; kultivační média; Humans; Biofilms